Feliz cumpleanos, Martin Luther King - Marzollo, Jean.; Pinkney, J. Brian (New York : Scholastic Inc., 1993)
An introduction to a great civil rights leader.
Translation of: Happy birthday, Martin Luther King.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; Civil rights workers -- Juvenile literature; Biographies; Literature